Integrated Nutrient Management on Panikachu in Joypurhat - Akther, MA; Hasan, T; Mollah, M RA; Rahman, MH; Islam, MA (Journal of Environmental Science and Natural Resources, 2021)
An experiment was conducted at the Multi location Testing (MLT) site, (medium highland under AEZ-25) Pachbibi, Joypurhat, Bogura district during rabi season of 2015-16. In the study, to evaluate the response of panikachu to different nutrient management practices under farmer’s field condition. There were five treatments viz. T1=Soil test based fertilizer dose (FRG 2012), T2=T1+ 25% NPK, T3=IPNS with 3 tha-1 poultry manure, T4= IPNS with 5 tha-1 cowdung, and T5= Farmers practice. The experiment was laid out in randomized complete block design (RCBD) with six dispersed replications.T3= IPNS with 3 t ha-1 poultry manure, T4 = IPNS with 5 t ha-1 cowdung, and T5= Farmers practice. The highest Panikachu rhizome yield (21.71 t ha-1), gross return (TK. 430185ha-1) and BCR (3.61) were found from T3 (IPNS with 3 t ha-1 poultry manure) which was followed by T5 (19.66 tha-1) T4 (19.45 tha-1), and statistically differed to other treatments. However, from results, it could be recommended that IPNS will be a promising technology for higher crop yields of Panikachu and profit as well as for the improvement of soil fertility and sustain soil productivity in Joypurhat region. Environ. Sci. & Natural Resources, 12(1&2): 29-32, 2019